Biochemistry of xenobiotics: towards a healty lifestyle and safe environment - Shamaan, Nor Aripin (Universiti Putra Malaysia Press, 2008)

(untitled)
Xenobiotics or foreign compounds include products of industry such as pesticides, industrial chemicals, synthetic drugs, antibiotics and heavy metals. Natural xenobiotics include animal poisons and toxins, antibiotics, drugs and toxic products from plants. These compounds may cause damage to living organisms resulting in deformities, DNA damage, poisoning or at the very least, a feeling of discomfort. In an environment contaminated by all these compounds, living organisms have managed to adapt by changing the way it reacts to the effects of these foreign compounds. They may modify the function of existing enzymes to catalyse reactions of xenobiotics or physically move to a less contaminated location. The cell as the smallest unit of life contains a diverse array of systems that effectively react to xenobiotics. This paper focuses on the biochemistry of the cell reacting to selected xenobiotics citing work done on insects, rats and mice and bacteria, in an effort to understand the underlying principles of xenobiotic metabolism.